The Anxiety of EFL Students in Presentation - Nur Lina Amalia; Nadiah Ma'mun (ELITE Association Indonesia, 2020)
This study investigatesat speaking anxiety of Students’Presentation. The subject of the study was freshmen in English Education Department. The method used in this study was qualitative. Forty one students were selected to be participants. The data were gathered through questionnaire and semi-structured interviews. The most commonly used tool for assessing FLA is the FLCAS (Foreign Language Classroom Anxiety Scale) developed by Horwitz et al. (1986). A modified version of FLCAS was used in this study. The original version of FLCAS is a 33-item, 5-point likert-scale instrument ranged from (strongly disagree to strongly agree) measuring students language anxiety.The result of the study showed that anxiety was exist in freshmen. It can be infered from the result of mean score of questionnaire’s result that the average score of student anxiety existence of FLCAS is in the existing class, which is 39.025. The result of contributing factors to students’ speaking anxiety during presentation were overthinking, lack of preparation, bad experience, low proficiency, low self- confidence, afraid of making mistakes, and test.So it is suggested that before having presentation, the students should be doing repeatred rehearsals and practice to eliminate the anxiety.